Sa ngalan ng ina: A short video feature - Ibarra, Rosa Lourdes (Animo Repository, 1996)
Sa Ngalan ng Ina is the story of the relationship between a daughter and her sickly mother. Pilar finds herself torn between her obligation to take care of her mother and her right to personal freedom. Feeling alone and trapped, she seeks refuge through her sketches. Her favorite subject is Kuliling, the crazy woman whom Pilar envies because she does not need to live up to anybody's expectation. Her desire for personal freedom and her mother's domineering personality push her to cause her mother's death. The stream of consciousness technique was employed to illustrate Pilar's fears and memories in the form of hallucinations. The project has a running time of 17 minutes and 12 seconds. Filipino was the language used and it was shot on a Hi-8 recorder using V8 tape. The editing format used was Betacam.